THE EFFECT OF SELF-CONGRUITY AND CELEBRITY ENDORSEMENT ON BRAND LOYALTY WITH BRAND ATTITUDE AS A MEDIATION VARIABLES - Parwati, Kardina Yudha; Rohman, Fatchur; Puspaningrum, Astrid (Universitas Brawijaya, Indonesia, 2021)
This research is conducted to analyze the effect of cognition and affection factors on consumer loyalty, the object used in this research is the consumer of local fashion product Cotton Ink. The main purpose of this research is to analyze and describe the relationship between self-congruity, celebrity endorsement, brand attitude, and brand loyalty. Besides, this research analyzes the role of brand attitude as the mediating variable of the relationship between self-congruity and celebrity endorsement toward brand loyalty. This research contribution is giving additional insight into the relationship between variables on the Cognition-Affect-Behavior Paradigms.